Communicative Action As Practiced by Pulo Kambing Garbage Community, East Jakarta Indonesia - Saktisyahputra SAKTISYAHPUTRA; Sunarto SUNARTO; Mikhael DUA (International Journal of Environmental, Sustainability, and Social Science, 2023)
Jakarta garbage volume increases every day. Each person produces 2.97 liters of waste per day from totally 1,849 tons in East Jakarta. According to State Minister for the Environment of The Republic of Indonesia Regulation local community is asked to involve in the waste management. This means the process of management can be taken under the communicative action according to local community lifeworld. This article will delve with communicative action as practiced by Pulo Kambing Garbage Community in East Jakarta in three sections: the first section is dealing with Juergen Habermas' concept of communicative action which is based on lifeworld; the second discusses the Pulo Kambing Garbage Community in East Jakarta; the third is dealing with theoretical and practical implications of the communicative action in dealing with the problem of waste management. The article concludes that the key success of reducing waste starts from the household participation. Any garbage community is rooted in such kind of household participation.